Anarchismo come educazione alla libertà. La prospettiva di Colin Ward tra educazione ambientale e partecipazione sociale - Stefania Maddalena; Valerio Ferro Allodola (Studi sulla Formazione)
For Colin Ward, anarchism is an act of social self-determination: all aspects of human existence and public life are characterized by large degrees of freedom. The school - institution dedicated quintessentially to the children’s education - ‘expands’ into other places: streets, playgrounds, meadows, woods, school buses, shops, become for Ward vital places that can offer extraordinary educational opportunities, promoting a model of libertarian education as an alternative to structured learning. An ‘environmental education’, in the double meaning of environment - instead of the classroom - as an educational medium and natural environment as a context to be studied; whose aim is to make young people not only masters of their own learning process, but also of the environment in which they live, through direct exploration and participatory education.